'To clasp hands...across the ocean': American woman suffragists in the Pacific World, 1893 – 1928 - Fapp, K (2024)
This thesis examines how American woman suffragists pursued the worldwide enfranchisement of women via transnational suffrage activism in the Pacific World between 1893 and 1928. Tracing suffragists and their goals as they forged and traversed transnational activist networks and imperial dynamics, it argues that these actions constituted acts of suffrage worldmaking which influenced the development of feminist internationalism and American empire in the Pacific.